Comparison between direct and reverse electroporation of cells in situ: a simulation study. Issue 6 (23rd March 2016) - Towhidi, Leila; Khodadadi, Delaram; Maimari, Nataly; Pedrigi, Ryan M.; Ip, Henry; Kis, Zoltan; Kwak, Brenda R.; Petrova, Tatiana W.; Delorenzi, Mauro; Krams, Rob
Abstract: The discovery of the human genome has unveiled new fields of genomics, transcriptomics, and proteomics, which has produced paradigm shifts on how to study disease mechanisms, wherein a current central focus is the understanding of how gene signatures and gene networks interact within cells. These gene function studies require manipulating genes either through activation or inhibition, which can be achieved by temporarily permeabilizing the cell membrane through transfection to deliver cDNA or RNAi. An efficient transfection technique is electroporation, which applies an optimized electric pulse to permeabilize the cells of interest. When the molecules are applied on top of seeded cells, it is called "direct" transfection and when the nucleic acids are printed on the substrate and the cells are seeded on top of them, it is termed "reverse" transfection. Direct transfection has been successfully applied in previous studies, whereas reverse transfection has recently gained more attention in the context of high‐throughput experiments. Despite the emerging importance, studies comparing the efficiency of the two methods are lacking. In this study, a model for electroporation of cells in situ is developed to address this deficiency. The results indicate that reverse transfection is less efficient than direct transfection. However, the model also predicts that by increasing the concentration of deliverable molecules by a factor of 2 or increasing the applied voltage by 20%, reverse transfection can be approximately as efficient as direct transfection. Abstract : Figure 4c and D show the difference in reversed and classical transfection of cells after variation of the concentration.